EKRANISASI UNSUR NARATIF DALAM FILM LIFE OF PI - Andini, Bertha Galuh; Hudoyo, Sapto (Seni Media Rekam ISI Surakarta, 2016)
Every year, films adapted from novels have developed significantly. However,there are many differences from their novels when the films screened, such as thereduction and addition of the storyline and characters, and also some variations.Thecreativity of the films toward their novels is because of the audio-visual medium,whilenovel caused by linguistic medium.Thus,there are certain plots that can be raised well inthe novel, but cannot appear in the film, or vice versa. This research examines theelement of narrative changes that covers the story, plot, characters, andcharacterizations in the movie entitled Life of Pi using ecranisation approach.Ecranisationtheory is an adapting novel to film that causes three changes; shrinking, adding, andvaried changes. This research adopts qualitative research method. The data wascollected by observation and literature study.The results showed that there were a lotof changes in this film include shrinking, that is the reduction and elimination of someplots,as well as the removal of the several characters.Also,there were some additionsand some changes.The function of the varied changes in this film is to create the processof causality consistently and also as a teaser.Keywords : Novel,film,ecranisation,and Life of Pi